Prevalence, risk factors, and management of dementia and mild cognitive impairment in adults aged 60 years or older in China: a cross-sectional study - Jia, Longfei; Du, Yifeng; Chu, Lan; Zhang, Zhanjun; Li, Fangyu; Lyu, Diyang; Li, Yan; Li, Yan; Zhu, Min; Jiao, Haishan; Song, Yang; Shi, Yuqing; et al. (The Lancet Public Health, 2020)
Background China has a large population of older people, but has not yet undertaken a comprehensive study on the prevalence, risk factors, and management of both dementia and mild cognitive impairment (MCI).